0
$\begingroup$

So i have a function: $$f:(-1,1) \rightarrow \mathbb{R} , f(x)= \frac{1}{\sqrt{(1-x)^3}}$$

I need to calculate it's taylor series(Maclaurin to be exact, because it's to be centered around x=0). And use that to either prove either disprove the following inequality(i presume it will be of help, i could be wrong though): $$\sqrt{1-x} \sum_{n=0}^{\infty} \frac{x^n}{(2n)!!} \leq \frac{1}{1-x} $$

double factorial meaning, so there is no confusion

Any help would be appreciated, thank you in advance.

$\endgroup$
  • 1
    $\begingroup$ The function is not defined for $x=1$. But you could write it as $(1-x)^{-3/2}$ to get the Maclaurin series $\endgroup$ – H. H. Rugh Aug 3 '16 at 8:09
  • $\begingroup$ i made a mistake, sorry, will edit $\endgroup$ – MathIsTheWayOfLife Aug 3 '16 at 8:15
  • $\begingroup$ @H.H.Rugh i made an edit, now it's defined correctly $\endgroup$ – MathIsTheWayOfLife Aug 3 '16 at 8:16
1
$\begingroup$

You may use the formula: $$ (1-x)^p = 1 + \sum_{k\geq 1} \frac{p \times \cdots \times (p-k+1)}{k \times \cdots \times 1} (-x)^k $$ valid for all $p$ and $|x|<1$ (or better)

$\endgroup$
  • $\begingroup$ will it help the inequality, or was it a long shot? $\endgroup$ – MathIsTheWayOfLife Aug 3 '16 at 8:29
  • $\begingroup$ Inequality doesn't hold, as you can see from my answer. $\endgroup$ – alans Aug 3 '16 at 8:42
  • $\begingroup$ As $(1-x)^{-3/2}=1-3/2x +...$, your sum starting with one should necessarily have the same linear term in order for the inequality to be valid for $x$ small. And this is not the case. $\endgroup$ – H. H. Rugh Aug 3 '16 at 9:10
0
$\begingroup$

Let $f(x) = (1-x)^{-3/2}$, then $$ f'(x) = \frac{3}{2}(1-x)^{-5/2} \\ f''(x) = \frac{5}{2}\frac{3}{2}(1-x)^{-7/2} \\ f'''(x) = \frac{7}{2}\frac{5}{2}\frac{3}{2}(1-x)^{-9/2} \\ $$ Now for $f^{(n)}$, we focus on the fraction in front : $$ Numerator = \frac{(2n+1)!}{2^n \cdot n!} \\ Denominator = 2^n $$ Therefore $$ f^{(n)}(x) = \frac{(2n+1)!}{4^n\cdot n!}(1-x)^{-n/2} $$ Now you can plug $x := 0$ and get your MacLaurin series !

$\endgroup$
0
$\begingroup$

Series expansion: $$(1-x)^{-\frac{3}{2}}=\sum_{n=0}^\infty (-x)^n\binom{-\frac{3}{2}}{n}$$ for $|x|<1$.

Since $$(2n)!!=2n(2n-2)\dots2=2^nn!,$$ inequality $$\sqrt{1-x} \sum_{n=0}^{\infty} \frac{x^n}{(2n)!!} \leq \frac{1}{1-x}$$ becomes $$\sqrt{1-x} \sum_{n=0}^{\infty} \frac{(\frac{x}{2})^n}{n!} \leq \frac{1}{1-x},$$ now use series expansion $e^t=\sum_{n=0}^\infty \frac{t^n}{n!}$, in order to get $$\sqrt{1-x} e^{\frac{x}{2}} \leq \frac{1}{1-x}.$$ But, this doesn't hold (check: for $x=-\frac{1}{2}$, it is equivalent with $e>9$, which doesn't hold), so we can conclude that initial inequality doesn't hold.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.